Evaluation of Physicochemical Characteristics of Smoked River Catfish Prepared from Fresh and Frozen Raws - Bustari Hasan; Desmelati Desmelati; Dian Iriani; Sumarto Sumarto; Sahyudi Sahyudi (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2016)
The aim of this study was to evaluate physicochemical characteristics of hotsmoked catfish from freshand frozen fish. River catfish samples (Hemibagrus nemurus Valenciennes, 1840), 240-270 gram in weightwere taken from catfish cage culture in Sungai Paku, Riau. A total fish samples (120 fishes) were groupedinto 4 batches, each batch consisted of 30 fish (15 fillets and 15 butterfly like cuts). One batch was smokedfresh and the other 3 batches were smoked after being frozen at -18oC for 10, 20 and 30 days respectively.Before smoked, the fish samples were analyzed for proximate composition and water holding capacity; andafter smoked, the fish samples were determined for smoking yield, proximate composition and sensoryquality. Moisture, fat and protein composition of fish was not different between fresh raw and frozen for10, 20 and 30 days (P>0.05), however, water holding capacity was higher for fresh than frozen fish; andthe value decreased as the longer the frozen storage (P<0.05). Smoking yield correlated stronger to waterholding capacity (r=0.59) than to moisture (r=0.01), fat (r=0.16) and protein (r=0.02) composition of theraw. Moisture, fat and protein of smoked fish was lower for smoked fish prepared from frozen fish than thatfor fresh fish (P<0,05); and the values decreased as the longer the frozen storage. Moisture, fat and proteinloss during smoking was higher for smoked fish prepared from frozen fish than that for fresh fish, exceptfor that frozen for 10 days. Overall, sensory values of smoked fish from frozen fish were lower than that forfresh fish (P<0,05); however, flavor and odor values were not different between smoked fish from fish frozenfor 10 days and fresh fish (P>0,05).